Empowering Farmers in Lagan Ulu Village through the Irrigation Water Use Improvement Acceleration Program (P3-TGAI) : Pemberdayaan Petani di Desa Lagan Ulu melalui Program Percepatan Peningkatan Tata Guna Air Irigasi (P3-TGAI) - Saputra, Rido; Aswandi, Aswandi; Indriyani, Indriyani; Fortuna, Dewi; Daulay, Diana Pebriani; Viyona, Melvi; Rohman, Fatkhul; Rasinta, Igef (Institut Riset dan Publikasi Indonesia, 2026)
The agricultural sector in Lagan Ulu Village faces productivity challenges due to irrigation damage and the absence of a management institution. This community service project aims to establish a Water User Farmers Association (P3A) and increase farmer capacity through the Irrigation Water Use Improvement Acceleration Program (P3-TGAI). The activity took place from July to September 2025 and used a participatory approach involving farmers, village officials, lecturers, and 10 KKNT students. The program stages included problem identification, outreach, deliberations with 17 core representatives of farmer groups, preparation of Articles of Association/Bylaws (AD/ART) and the Budget Work Plan (RKA), legalization, and monitoring and evaluation. As a result, a formal organization,